Boethius on mind, grammar, and logic : a study of Boethius' Commentaries on Peri hermeneias - Suto, Taki. (Philosophia Antiqua, 2012)
Boethius (c.480-c.525/6), who is best known for his Consolation of Philosophy , has been accused of misinterpreting Aristotle's logical works in his translations and commentaries thereof. Building on recent scholarship in the philosophy of late antiquity, this book challenges some of the past interpretations of Boethius and reveals significant features of his semantics and logic. With comparisons between his and contemporary arguments and attention to the terminology of late antiquity, this work is of use to those interested in semantics, logic and grammar from antiquity to the modern day. Furthermore, this book's new conclusions aim to reinvigorate interest in this much-maligned and poorly understood philosopher.